2015
DOI: 10.3762/bjoc.11.272
|View full text |Cite
|
Sign up to set email alerts
|

Versatile synthesis and biological evaluation of novel 3’-fluorinated purine nucleosides

Abstract: SummaryA unified synthetic strategy accessing novel 3'-fluorinated purine nucleoside derivatives and their biological evaluation were achieved. Novel 3’-fluorinated analogues were constructed from a common 3’-deoxy-3’-fluororibofuranose intermediate. Employing Suzuki and Stille cross-coupling reactions, fifteen 3’-fluororibose purine nucleosides 1–15 and eight 3’-fluororibose 2-chloro/2-aminopurine nucleosides 16–23 with various substituents at position 6 of the purine ring were efficiently synthesized. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…To avoid elimination reactions and the formation of side products during the fluorination step, it was reported that the reaction had to be performed on a precursor bearing unprotected trans diol. 10 , 11 Therefore, l -xylose glycoside 9 was treated with DAST to afford the fluorinated product in 54% yield. In agreement with the literature, 6 , 7 we observed the regioselective formation of 3-fluoro- l -ribofuranoside 10 .…”
Section: Resultsmentioning
confidence: 99%
“…To avoid elimination reactions and the formation of side products during the fluorination step, it was reported that the reaction had to be performed on a precursor bearing unprotected trans diol. 10 , 11 Therefore, l -xylose glycoside 9 was treated with DAST to afford the fluorinated product in 54% yield. In agreement with the literature, 6 , 7 we observed the regioselective formation of 3-fluoro- l -ribofuranoside 10 .…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent this problem, current strategies that have been developed for the preparation of 6-heteroaryl guanosines require the use of the expensive 6-iodo-2-aminoguanosine ( 2 ) substrate, ,, prepared from 1 via Finkelstein reaction . Cross-coupling strategies such as Stille, Negishi, and other bespoke variants , of these have been explored using both 1 and 2 . However, the toxicity associated with organotin reagents and the presence of a number of Lewis basic sites and electrophilic O-protecting groups have limited their broader utility.…”
mentioning
confidence: 99%
“…The guanidine system is present in structural components of biomolecules, namely in the amino acid arginine or in the nucleobase guanine. It is also embodied in the nitrogenous aromatic moiety of various bioactive compounds, such as in the 2aminopurine motif, which is contained in the antibiotic natural nucleosides amipurimycin and miharamycins [22,23], and in various synthetic nucleosides exhibiting anticancer [24] and antiviral properties [25], or in the 2-aminopyrimidine moiety, which is present in the anticancer drug imatinib [26]. On the other hand, the amidine (or imidamide) system (NH2-C=NR) contained in the guanidine group is present in the cytosine and adeninebased motifs, which are found in various nucleoside analogues used as chemotherapeutic agents [27,28].…”
Section: Introductionmentioning
confidence: 99%